A predictive analysis of STEM vocation through students’ attitudes to school science classes - María-Antonia Manassero-Mas; Ángel Vázquez-Alonso (Frontiers in Education)
IntroductionThe increasing strategic, economic, social and personal value of scientific, technological, engineering and mathematical (STEM) knowledge in current societies highlights the need for STEM professionals. However, the enrolment rates in STEM careers are decreasing, particularly for some STEM specialties, women, and minorities. This lack of STEM vocation has led to worldwide concern, warranting its research, as many factors may influence career decisions. This study analyses the relationships between students’ perceptions of several characteristics of secondary school science classes and their intentions to enroll in STEM careers. It develops a gender perspective on the issue.MethodsThe quantitative methodology surveys thousands of Spanish 15-year-old students who completed the Relevance of Science Education Second (ROSES-Q) questionnaire from 2021 to 2023. Some items about vocational intentions and school science classes were drawn from the ROSES-Q to explore the abovementioned relationships through linear regression analysis.ResultsThe results show that students’ intentions to pursue STEM careers approximately amount to one-third of the sample, and boys’ rates are significantly higher than girls’ rates. The items of school science classes reached their agreement peak in “science is interesting,” “increased my curiosity” and “the importance of science for our way of life,” whereas “becoming more critical and skeptical” obtained the lowest score. Most gender differences in these items were not statistically significant. Six school science class items significantly predicted the students’ degree of STEM vocation by sharing 46.1% of their common variance. In decreasing order of prediction power, the six significant predictors are “liking school science better than most other subjects,” “helping to understand sustainability solutions,” “becoming more critical and skeptical,” “importance of science for our way of life,” “difficulty of school science,” and “opening my eyes to new and exciting jobs.”DiscusionThe implications of this study for promoting STEM vocations suggest that teachers carefully cultivate those relevant characteristics of school science classes through appropriate pedagogies and inclusive and equitable contexts for all, especially for girls.